2022
DOI: 10.3390/cells11182778
|View full text |Cite
|
Sign up to set email alerts
|

Targeting HSP90 as a Novel Therapy for Cancer: Mechanistic Insights and Translational Relevance

Abstract: Heat shock protein (HSP90), a highly conserved molecular chaperon, is indispensable for the maturation of newly synthesized poly-peptides and provides a shelter for the turnover of misfolded or denatured proteins. In cancers, the client proteins of HSP90 extend to the entire process of oncogenesis that are associated with all hallmarks of cancer. Accumulating evidence has demonstrated that the client proteins are guided for proteasomal degradation when their complexes with HSP90 are disrupted. Accordingly, HSP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 255 publications
0
28
0
Order By: Relevance
“…The cytoplasmatic HSP90 alpha and beta‐isoforms are upregulated in various types of cancer and HSP‐90 together with its co‐chaperones seem to play an important role in metastatic behavior 17,18 . HSP‐90 inhibitors such as geldanamycin are under clinical trials as cancer therapeutics with promising results 18 . Leukotriene A‐4 hydrolase is an important regulator of inflammation and is overexpressed in many types of cancer cells.…”
Section: Resultsmentioning
confidence: 99%
“…The cytoplasmatic HSP90 alpha and beta‐isoforms are upregulated in various types of cancer and HSP‐90 together with its co‐chaperones seem to play an important role in metastatic behavior 17,18 . HSP‐90 inhibitors such as geldanamycin are under clinical trials as cancer therapeutics with promising results 18 . Leukotriene A‐4 hydrolase is an important regulator of inflammation and is overexpressed in many types of cancer cells.…”
Section: Resultsmentioning
confidence: 99%
“…It is urgent for us to find new drug treatments and drug targets in conflict with obesity and pertinent metabolic disorders. In the last ten years, HSP90 has become a major therapeutic target for cancer [ 23 ], neurodegenerative disorders [ 24 ], anti-viral [ 25 ], and anti -osteoclastogenesis [ 26 ]. Although there are promising opportunities in utilizing HSP90 inhibitors for treating illnesses, the role of four paralogs from the HSP90 chaperone family in diseases is still not well comprehended.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, several studies have shown with neuroendocrine cell lines, xenograft models and patient-derived SI-NET tumor cells that inhibitors of HSP90 can potentiate the tumor cell killing effect of radiotherapy ( 18 , 19 , 25 , 26 ). Indeed, several HSP90-targeted drugs have been reported and studied in preclinical and clinical models ( 23 , 27 ). However, none of these HSP90 inhibitors are in clinical use for the treatment of any cancer type due to dose-limited toxicity, drug resistance and poor bioavailability.…”
Section: Discussionmentioning
confidence: 99%